Evaluasi Kecukupan Panas dan Pengembangan Proses Alternatif dalam Sterilisasi Komersial Jamur Kancing dalam Kaleng - Feri Kusnandar; Huda Hainun Dafiq; Winiati P. Rahayu; Dandy Irmawan (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2023)
. This research aimed to evaluate the adequacy of heat treatment and redesign the commercial sterilization process for canned button mushrooms to ensure that the product meets the minimum sterilization requirement without undergoing excessive processes. The study conducted tests on heat distribution and penetration, calculated the sterilization value (F0) using the trapezium and Ball methods, and designed an alternative sterilization process to avoid excessive procedures. The sterilization process for canned mushrooms, with a can dimension of 300x407, involved a temperature of 132°C for 16 minutes, resulting in an F0 value of 161.7 minutes. This value far exceeds the required minimum F0 value. To optimize the process, an alternative sterilization procedure was developed. It involved a temperature of 126°C, a process time of 10 minutes, and an initial product temperature of 40–50°C. This alternative process yielded an F0 value of 10 minutes. Furthermore, additional alternative process conditions were designed, with considerations to various process times (Pt), initial temperatures (Ti), retort temperatures (TR), and F0 values.